Characters with Disabilities in Brazilian Telenovelas: Almost Invisible Consumers (Global Journal of Management and Business Research, 2014)
Although important vehicles of culture and of society's values and perspectives, cultural texts represent little explored possibilities in the research focusing on the behavior of consumers with disabilities. In Brazil, telenovelas, or evening TV drama series, present as suitable cultural texts for such studies, in view of the importance of this type of programming as material that both crosses class lines and has national penetration. The objective of this study was to discuss how the consumption decisions and practices of people with disabilities are presented in Brazilian telenovelas. To achieve the objective, 22 Brazilian telenovela scenes showing characters with disabilities in situations of consumption were reviewed. The results of the study call attention to the need for companies, public institutions and society in general to review how they address these almost invisible consumers, who are often overlooked as potential customers and excluded from public policy actions.
Keywords: people with disabilities; cultural texts; brazilian telenovela; consumer behavior; qualitative research